IMPLEMENTASI DAN ASESMEN PEMBELAJARAN BERDIFERENSIASI PADA MATERI ANEKDOT UNTUK SISWA SMA - Yuanita Widiastuti; Abdul Rani; Sri Wahyuni (STKIP Siliwangi, 2023)
This study aims to describe the implementation and assessment of differentiated learning on anecdotal material for high school students by reviewing the alignment of predetermined learning instruments. The design in this study is a mix method. The data collection procedure was carried out by researchers by distributing questionnaires and interviewing Indonesian language teachers in class X as respondents. Respondents filled out the prepared questionnaire using the Google Form format. Data analysis was carried out descriptively. The findings of the differentiated learning assessment research on content differentiation components are well implemented. The assessment of the process differentiation component was implemented well in two aspects, namely the implementation of the way in which the material was delivered varied according to students' understanding abilities and there were variations in activities to understand the material based on the container. Three aspects of the assessment indicators are still experiencing differentiation. Differentiated learning assessment on product differentiation components is well implemented. The results of the research on the implementation of differentiated learning assessments on anecdotal material for high school students serve as a guideline for Indonesian teachers in conducting assessments in favor of learning profiles.